(untitled) (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
Social reintegration is an important component of the correctional system because the success of punishment is determined not only by the completion of a sentence but also by the ability of former prisoners to return to and participate in community life. However, social stigma and the label “former prisoner” may persist after the completion of a sentence, potentially resulting in social exclusion, discrimination, and difficulties in accessing employment and rebuilding social relationships. This study aims to analyze social stigma against former prisoners and identify the forms and barriers to social reintegration from a criminological perspective. This study employs normative juridical legal research with a descriptive-analytical design through statutory, conceptual, and criminological approaches. Research materials were obtained through a literature review of legislation, books, scientific journal articles, and previous studies, and were analyzed qualitatively using Labeling Theory, Social Exclusion Theory, and Reintegrative Shaming Theory. The findings indicate that stigma can develop from a labeling process into social exclusion that restricts former prisoners’ access to employment, social relationships, and community participation. The integration of the three theoretical perspectives contributes to a more comprehensive understanding of the relationship between labeling, social exclusion, and reintegration barriers. The study concludes that successful reintegration depends not only on individual readiness but also on social acceptance, community support, and opportunities for former prisoners to resume productive social functions. These findings emphasize the importance of strengthening social-based reintegration policies to reduce stigma and support the prevention of recidivism.